A influência de detritos lenhosos na morfologia e na sedimentologia de leito no rio Guabiroba, Guarapuava - Pr - Binda, Andrey Luis (2009)
Trees, twigs and leaves fallen inside of the channel, form a significant component of the fluvial environment and natural occurrence in fluvial systems that cut forested areas. All these vegetal materials that are found inside of the channel are called wood debris. The wood debris play a key function in the ecology and geomorphology of channels, being able to affect the processes of the channels in an ample reach: since the hydraulic roughness, retention and sized grain of bed sediments, until the creation of steps and pools, being able to the times to control the standard of the channel and distance and/variation of fluvial features that are basic for the formation of aquatic habitat. In this context, the present research had as objective, to verify the influence of accumulations of wood debris on the morphology and sedimentology of stream bed in the river Guabiroba, Guarapuava, Center-South of the Paraná. The used techniques had included: installation of permanent transversal profiles (to the upstream and downstream of the accumulations) and sections of batimetric measurement, survey of the longitudinal profile and grain sized characterization of bed sediments. The measurement was carried throughout 15 months (December of 2007 the March of 2009) in four sections located in the main course of the river. The rainfall during the measurement allowed to particularizing the occurrence of only one period with rains above average (3 - 4ª Campaign). The results indicate the occurrence of sedimentation in the second and fifth measurement and processes of erosion in the third and fourth measurement. These processes erosive-depositional can in part be attributed to the pluviometric regime, with the periods of high entailed concentration of rains to the erosion of the stream bed and periods of related scarce and not concentrated rains with the deposition of sediments. The analysis of the data allows to establish some consideration: 1) predominance of processes of erosion in the sections of batimetric measurement; 2) bigger rate deposition in downstream cross-sectional profiles of the accumulations; 3) predominance of coarser sediments (gravel medium - sand very coarse) to upstream and finer sediments (gravel fine - sand medium) to downstream; 4) bigger diversity of depths in the immediacy of the accumulations; 5) establishment of riffles by the forced deposition of sediments and pools for the scour of the stream bed.